Postoperative Spondylodiscitis: A Case Report - Şafi Edemci; Fügen Oktay; Canan Çelik (Archives of Rheumatology, 2006)
Postoperative spondylodiscitis (POS) occurs most often after disc surgery and is regarded as a serious and significant clinical problem. There are no hematologic, biochemical, or imaging findings that are unequivocally diagnostic of this process. The diagnosis of POS must be considered after any invasive procedure performed on the spine with a history of worsening back pain in the absence of constitutional symptoms. In this case report, a patient who had spondylodiscitis and bilateral polyradiculopathy after lumbar disc sugery was presented. (Rheumatism 2006; 21: 121-4)